Age disparities in transplantation. Issue 5 (October 2021) - Melandro, Fabio; Del Turco, Serena; Ghinolfi, Davide
Abstract : Purpose of review: The aim of this review is to outline disparities in liver and kidney transplantation across age spectrum. Disparities do not involve only recipients whose age may severely affect the possibility to access to a potentially life-saving procedure, but donors as well. The attitude of transplant centers to use older donors reflects on waiting list mortality and drop-out. This review examines which age categories are currently harmed and how different allocation systems may minimize disparities. Recent findings: Specific age categories suffer disparities in the access to transplantation. A better understanding of how properly evaluate graft quality, a continuous re-evaluation of the most favorable donor-to-recipient match and most equitable allocation system are the three key points to promote 'justice and equality' among transplant recipients. Summary: The duty to protect younger patients waiting for transplantation and the request of older patients to have access to potentially life-saving treatment urge the transplant community to use older organs thus increasing the number of available grafts, to evaluate new allocation systems with the aim to maximize 'utility' while respecting 'equity' and to avoid 'futility' thus minimizing waiting list mortality and drop-out, and improving the survival benefits for all patients requiring a transplant. Video abstract: http://links.lww.com/COOT/A9 Abstract : Supplemental Digital Content is available in the text